Infant toenails as a biomarker of in utero arsenic exposure - Davis, Matthew A. (2014)
A growing body of evidence suggests that in utero and early-life exposure to arsenic may have detrimental effects on children, even at the low to moderate levels common in the United States and elsewhere. In a sample of 170 mother–infant pairs from New Hampshire, we determined infant exposure to in utero arsenic by evaluating infant toenails as a biomarker using inductively coupled plasma mass spectrometry. Infant toenail arsenic concentration correlated with maternal postpartum toenail concentrations (Spearman’s correlation coefficient 0.34). In adjusted linear models, a doubling of maternal toenail arsenic concentration was associated with a 53.8% increase in infant toenail arsenic concentration as compared with 20.4% for a doubling of maternal urine arsenic concentration. In a structural equation model, a doubling of the latent variable integrating maternal toenail and urine arsenic concentrations was associated with a 67.5% increase in infant toenail arsenic concentration. A similar correlation between infant and maternal postpartum toenail concentrations was observed in a validation cohort of 130 mother–infant pairs from Rhode Island. In utero exposure to arsenic occurs through maternal water and dietary sources, and infant toenails appear to be a reliable biomarker for estimating arsenic exposure during the critical window of gestation.